3sin2x- (корень3) cos2x=0

3sin2x- (корень3) cos2x=0
Гость
Ответ(ы) на вопрос:
Гость
6sinx*cosx-(корень3)*(cosx)^2+(корень3)(sinx)^2=0  |:(cosx)^2  однородное уравнение 2 степени (корень3)(tgx)^2+6tgx-(корень3)=0   |*(корень3) 3(tgx)^2+6(корень3)tgx-3=0       |:3 (tgx)^2+2(корень3)tgx-1=0 D=12+4=16 tgx=(-2(корень3)-4)/2= -(корень3)-2          или     tgx=(-2(корень3)+4)/2= -(корень3)+2 x= -arctg((корень3)+2) + пи*n                             x=arctg(-(корень3)+2)+ пи*n   НЕ УВЕРЕНА, ЧТО ПРАВИЛЬНО
Не нашли ответ?
Ответить на вопрос
Похожие вопросы